“Your flowing locks are like purple” (Song 7,5): Hair and Hair Colour in the Hebrew Bible - Gudme, Anne Katrine de Hemmer (Scandinavian journal of the Old Testament, 2025)
This study is a survey of descriptions of hair and specifically hair colour in the Hebrew Bible. It is an exploration of the phenomenology of hair in the Hebrew Bible, and of how hair “speaks” in these texts and communicate messages of social status, of aesthetics and beauty, gender and power. First, I shall give an introduction to hair in the Hebrew Bible more generally by exploring the relationship between hair and ritual and between hair and concepts of beauty. Then, I shall look into three case-studies that mention the colour of hair specifically: Esau in Gen 25 and 27; references to hair colour and appearance in three passages in the Song (4,1; 5,11; 7,6) and descriptions of grey hair in a number of Hebrew Bible texts. I explore these texts to determine how they inform us of social and aesthetic values in the Hebrew Bible and of the hierarchies that these values indicate.